(untitled) (International Journal of Food and Nutritional Sciences, 2025)
Malnutrition remains a significant clinical and public health concern, particularly for patients undergoing chemotherapy. An accurate and timely diagnosis is essential for initiating appropriate nutritional interventions. To assess the association between the GLIM criteria and PG-SGA in identifying malnutrition among patients undergoing chemotherapy in a day-care setting, and to evaluate the diagnostic performance of GLIM using PG-SGA as the reference standard. A cross sectional study was conducted on 63 chemotherapy patients in the chemo ward. Nutritional assessments were performed using the PG-SGA, NRS-2002, and GLIM criteria. Phenotypic and etiological data were collected, including body mass index (BMI), weight loss, food intake, and handgrip strength. Statistical analyses were performed using the SPSS (version 24). Pearson Chi Square test were applied to evaluate the association between PG-SGA and GLIM scores. ROC curve analysis was conducted to evaluate the diagnostic accuracy of the GLIM criteria using the PG-SGA as the reference standard. The Area Under the Curve (AUC) with 95% Confidence Interval (CI) was reported, and an optimal PG-SGA score range was determined based on the sensitivity and specificity balance. The study included 63 chemotherapy patients (mean age 60.76 ± 9.27 years; BMI 24.92 ± 6.09 kg/m²).PG-SGA scores averaged 8.49 ± 4.45. Based on the NRS 2002, 22.2% of the patients were at risk of malnutrition. The PG-SGA classified 46.0% as moderately and severely malnourished, while the GLIM identified 20.6% as malnourished. A significant association was found between the tools (Chi-square = 9.816, p = 0.002), which PG SGA being more sensitive. The GLIM showed good diagnostic accuracy (AUC = 0.660, p = 0.029). An optimal PG-SGA score of 4.5–9.5 balanced sensitivity and specificity. GLIM can effectively complement nutritional screening in oncology. The study concluded that the PG-SGA is more sensitive in detecting malnutrition, while the GLIM provides good diagnostic accuracy and significant association with the PG-SGA.